Educação profissional para a juventude: o programa Jovem Aprendiz como modelo de aprendizagem - Aguiar, Ruth Braga de (2010)
A society in full social development is formed with youth and children having their duties and rights guaranteed and respected. Access to an eficacious education for life in society and access to jobs are what young people and the work market are expecting. That is why public policies aimed at youth should not have an assistencialist character which does not solve the problem at its roots, but should propitiate a path to elevate schooling and the possibilities of employability, either by qualifying or by creating more jobs. For this, education, be it professionalizing (technical qualification among others) or basic, is a valuable ally in forming an active subject capable of competing in the work world and of being a citizen.